Optimization of Hydrogen Combustion in Diesel Engines: A CFD-Based Approach for Efficient Hydrogen Mixing and Emission Reduction - Bogdan Suatean; Grigore Cican; Stephane Guilain; Guillermo De-Paz-Alcolado (Fuels)
Hydrogen internal combustion engines (ICEs) have gained significant attention as a promising solution for achieving zero-carbon emissions in the transportation sector. This study investigates the conversion of a 2 L Diesel ICE into a lean hydrogen-powered ICE, focusing on key challenges such as hydrogen mixing, pre-ignition, combustion flame development, and NOx emissions. The novelty of this research lies in the specific modifications made to optimize engine performance and reduce emissions while utilizing the existing Diesel engine infrastructure. The study identifies several important design changes for the successful conversion of a Diesel engine to hydrogen, including the following: Intake port design: transitioning from a swirl to a tumble design to enhance hydrogen mixing; Injection and spark plug configuration: using a lateral injection system combined with a central spark plug to improve combustion; Piston design: employing a lenticular piston shape with adaptable depth to enhance mixing; Mitigating Coanda effect: preventing hydrogen issues at the spark plug using deflectors or caps; and Head design: maintaining a flat head design for efficient mixing, while ensuring adequate cooling to avoid pre-ignition. These findings highlight the importance of specific modifications for converting Diesel engines to hydrogen, providing a solid foundation for further research in hydrogen-powered ICEs, which could contribute to carbon emission reduction and a more sustainable energy transition.